(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze several factors related to coping strategies for academic stress among students of the Faculty of Foreign Languages, Thang Long University, in the 2021–2022 academic year. Methods: A cross-sectional descriptive study was conducted on 452 students from the Faculty of Foreign Languages, Thang Long University. Results: Students majoring in English, with average or above-average economic conditions, living independently, not under academic pressure from family, and who had not repeated any courses in the previous semester were more likely to adopt approach coping strategies (p<0.05). In contrast, students majoring in Japanese and those experiencing academic pressure from lecturers or family tended to use avoidant coping strategies (p<0.05). Additionally, students under pressure from lecturers were more likely to seek social support as a coping mechanism. Conclusion: Students’ coping strategies for academic stress are influenced by both individual and environmental factors. Targeted psychological interventions are needed, particularly for at-risk student groups.